(3JMUjd GdSYGOIs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3CeG Cf GdSYGOI gi ZGjI eG jJThbgG cd EfSGf s
(3BNQgG (B:s
(3abO jfHZi Cf jaJMM cJGHkG ef cJH GdChGFd Hg jSgd GdTQhY ai gPg GdUfGYI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdMGOi YTQs
(3GfXQg eY GdeNWhW Qbe (B305s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(11 / 240) s
Keywords: (3GdadSaI hGdefWbs